The Kingdom by the sea : a journey around the coast of Great Britain - Theroux, Paul, 1941- (Penguin Books, 2000)
After eleven years as an American living in London, the renowned travel writer Paul Theroux set out to travel clockwise around the coast of Great Britain to find out what the British were really like. The result is this perceptive, hilarious record of the journey. Whether in Cornwall or Wales, Ulster or Scotland, the people he encountered along the way revealed far more of themselves than they perhaps intended to display to a stranger. Theroux captured their rich and varied conversational commentary with caustic wit and penetrating insight.